New insight into the aptamer conformation and aptamer/protein interaction by surface-enhanced Raman scattering and multivariate statistical analysis. Issue 29 (12th July 2021) - Safar, Wafa; Tatar, Andra-Sorina; Leray, Aymeric; Potara, Monica; Liu, Qiqian; Edely, Mathieu; Djaker, Nadia; Spadavecchia, Jolanda; Fu, Weiling; Derouich, Sarra Gam; Felidj, Nordin; Astilean, Simion; et al.
Abstract : Combining SERS and statistical analysis, we demonstrated that an aptamer is a flexible molecule that is blocked in a specific conformation to capture its analyte and we provided evidence for the dynamics of the aptamer/protein interaction. Abstract : We study the interaction between one aptamer and its analyte (the MnSOD protein) by the combination of surface-enhanced Raman scattering and multivariate statistical analysis. We observe the aptamer structure and its evolution during the interaction under different experimental conditions (in air or in buffer). Through the spectral treatment by principal component analysis of a large set of SERS data, we were able to probe the aptamer conformations and orientations relative to the surface assuming that the in-plane nucleoside modes are selectively enhanced. We demonstrate that the aptamer orientation and thus its flexibility rely strongly on the presence of a spacer of 15 thymines and on the experimental conditions with the aptamer lying on the surface in air and standing in the buffer. We reveal for the first time that the interaction with MnSOD induces a large loss of flexibility and freezes the aptamer structure in a single conformation.